Stock price contagion effects of low-quality audits at the individual audit partner level - GUL, Ferdinand A. (Institutional Knowledge at Singapore Management University, 2019)
We use Chinese audit partner data to show that partners associated with financial reporting fraudinduce share price declines among non-fraudulent firms audited by the same audit partners. In cross-sectionalanalyses, we find that share price declines are more pronounced when low-quality partners (LQPs) failed to issuemodified audit opinions during the period in question and when the LQPs were from one of the Top 10 audit firms.Additional analyses show that investors impose larger penalties on contagion firms when fraudulent firms are largerand the time lapse between sanction and fraud commitment is shorter. The personal characteristics of LQPs (exceptgender) do not cause a difference in market reaction to contagion firms. Overall, our results speak to the importanceof audit partner identity to stock market valuation.